Microglia respond to exogenous and endogenous activating stimuli differently during development - Edan, Rawan (2020)
Background: Glial cells (microglia and astrocytes) facilitate inflammatory responses in the CNS by responding to pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs). Dysregulation in their communication could affect their polarisation state and if not resolved, can give rise to the pathogenesis of several neurodegenerative disorders. The different morphologies acquired by microglia during development suggest a functional difference crucial for the development of the brain. During ageing microglial state is skewed to a pro-inflammatory phenotype. Lipopolysaccharide (LPS) stimulation of aged microglia augments gene expression of pro-inflammatory mediators. The extent of glial cell activation and their production of inflammatory mediators affects the fate of neurons. LPS stimulation of microglia caused death in neurons mediated by neurotoxic glial cross-talk. Microglial response to injury alters their physiological release of neuroprotective brain-derived neurotrophic factor (BDNF) and its persistent release from ATP-activated microglia via P2X4R can contribute to neuropathic pain. In this thesis, we investigated microglial sensitivity during development towards LPS and ATP and regional heterogeneity. We studied the effect of LPS on glial cell communication in early post-natal and adult microglia, and the impact of consequent produced inflammatory mediators on neuronal viability. We also compared the inflammatory state of adult and neonatal microglia in response to ATP. Orphan nuclear receptor NR4A subfamily members have anti-inflammatory properties during neuroinflammation carried out by microglia and astrocytes. In this thesis, we studied their expression in response to PAMPs and DAMPs. Methods: Sprague Dawley rats have been used for all primary cultures. Neonatal cortical or spinal cord microglia or astrocytes primary cultures were established from P 0-2 rats while P-40 rats were used for cortical or spinal cord adult primary microglia cultures. Cortical neurons were isolated from E18 rats. Serum or serum-free media were used to evaluate the effect of serum on gene expression. Microglia were treated with 100 ng/ml LPS. Astrocytes were incubated with LPS-stimulated microglia-conditioned media (MCM) for 1, 3, 6 and 24h. Real-time qPCR was performed to evaluate Nur77, Nurr1, NOR-1, IL-1β and TGF- β transcript levels in astrocytes in response to MCM stimulation. Primary cortical neurons were incubated with serum-free MCM-stimulated astrocyte’s conditioned media for 24 hours and their viability was evaluated. In chapter four, adult or neonatal spinal cord or cortical microglia were stimulated with different concentrations of ATP and the effect of pretreating them with P2X inhibitor (TNP-ATP) or p38 MAPK inhibitor (SB202190) was evaluated. Immunoreactivity of P2X4R in adult and neonatal microglia was investigated. BDNF expression (through qPCR) and release (via ELISA) was determined in response to ATP stimulation and inhibitors. The anti-inflammatory mediators, Nurr1 and IL-10 mRNA expression in response to ATP and inhibitors were also studied in adult and neonatal microglia. Results: LPS stimulation increased cortical (adult: 32-fold, neonatal:413-fold) and spinal cord (neonatal: 5-fold) microglial Nur77 mRNA expression and also NOR-1 mRNA expression rapidly in cortical (adult: 5-fold and neonatal: 57-fold) and spinal cord microglia (neonatal: 98-fold). Astrocytes orphan nuclear receptors mRNA levels significantly increased when stimulated with neonatal or adult MCM for 24 hrs. Adult cortical LPS-stimulated MCM appeared to increase the level of IL-1β mRNA (59-fold) in a higher manner compared to astrocytes stimulated with neonatal cortical LPS-stimulated MCM (12-fold) in serum rich media and the same effect was notable in spinal cord astrocytes treated with spinal cord MCM. Levels of MCM-induced NOR-1 mRNA was higher (~ 100-fold in cortical astrocytes and ~ 60-fold in spinal cord astrocytes ) than Nur77 (~15-fold in spinal cord astrocytes and ~80-fold in cortical astrocytes) and Nurr1 transcript levels (~13-fold in spinal cord astrocytes and ~55-fold in cortical astrocytes. Morphological observations based on neuronal axons integrity suggested that neonatal cortical microglia promoted proliferation in cortical neurons sustained by cortical astrocytes conditioned media (ACM). Cell proliferation assay confirmed that neonatal cortical MCM-ACM increased the viability (153%) of cortical neurons in comparison to controls (99%) and adult unstimulated-MCM-ACM (150%) or LPS-stimulated MCM-ACM (122%) treated. Microglial stimulation with ATP significantly up-regulated NR4A subfamily members after 1 hour of stimulation in cortical and spinal cord microglia. ATP stimulation significantly up-regulated BDNF expression levels in adult microglia (4-fold in spinal cord and 4.8-fold in cortical) and not neonatal microglia (1.6-fold in spinal cord and 1.4-fold in cortical). Pre-treatment with TNP-ATP down-regulated mRNA expression (≤ 3-fold) and release of BDNF in adult cortical and spinal cord microglia while p38 MAPK inhibitor down-regulated ATP –induced BDNF transcript levels (3-fold) but failed to significantly reduce BDNF release from adult cortical and spinal cord microglia. Pre-treatment with both inhibitors attenuated ATP-induced Nurr1 and IL-10 expression in adult and neonatal microglia. Conclusion: The extent of microglial activation and their polarisation is dependent on the type, duration and concentration of the stimulus. Microglial developmental and regional heterogeneity was evident in the event of external (LPS) and endogenous (ATP) stimuli. Glial cell communication and their responses to activating stimuli are modulated by both developmental stage and physical location.